Correlation of EYS polymorphisms with lumbar disc herniation risk among Han Chinese population - Ji, Demin (Mol Genet Genomic Med, 2019)
BACKGROUND: Lumbar disc herniation (LDH) is a common spinal disease in clinical practice. Once lumbar disc herniation occurs, it seriously reduces patient's quality of life. The EYS (eyes shut homolog) was discovered in recent years and it may be related to lumbar disc herniation. So we conducted a case–control study to explore the relationship between EYS polymorphism and lumbar disc herniation risk. METHODS: We selected 5 single‐nucleotide polymorphisms (SNPs) of EYS gene in a case–control study with 508 cases and 508 healthy controls to evaluate the relatedness by using genetic model, haplotype, and stratification analysis. RESULTS: We found that the minor alleles of rs62413038 (OR = 1.21, 95%CI: 1.01–1.43, p = .036) and rs9450607 (OR = 1.26, 95% CI: 1.05–1.53, p = .016) were associated with an increased risk of lumbar disc herniation in the allelic model analysis. In the genotypic model analysis, rs62413038 displayed a significantly increased risk of lumbar disc herniation in log‐additive models (OR = 1.20, 95% CI: 1.01–1.43, p = .039). While the rs9450607 was also obviously associated with an increased lumbar disc herniation risk in recessive (OR = 1.98, 95% CI: 1.24–3.13, p = .004) and log‐additive models (OR = 1.27, 95% CI: 1.05–1.55, p = .014). In addition, in the haplotype analyses of the SNPs, we found that the “CGGA” haplotype of rs1482456, rs9342097, rs9450607, and rs7757884 was associated with lumbar disc herniation. (OR = 0.52, 95% CI: 0.30–0.89, p = .017). CONCLUSION: These results suggest that EYS polymorphism may be associated with lumbar disc herniation among Han Chinese population. It also opens up a new exploration direction for the etiology of lumbar disc herniation.